Provision of Labor Resources for the Construction of Irrigation and Reclamation Facilities in tthe Bukhara Region in the 1950s–1960s: Patterns and Impacts of Agricultural Migration - Mirshakarovich, Mirzoev Sharifjon (Indonesian Journal Publisher, 2025)
This study investigates the provision of labor resources for the construction of irrigation and reclamation facilities in the Bukhara region during the 1950s and 1960s, focusing on internal agricultural migration influenced by Soviet state policies. The research aims to examine the mechanisms, socio-economic consequences, and challenges of resettlement processes, as well as their broader impact on regional development in Soviet Uzbekistan. Using the historical-genetic method, archival documents, official Soviet-era decrees, and contemporary media sources were analyzed. The findings reveal significant discrepancies between resettlement and placement plans, which resulted in failures to retain migrant populations in new territories. The disorganization in household selection, implementation gaps, and delays in distributing promised benefits such as housing, loans, and tax exemptions led to mass returns of migrants. The study concludes that centrally planned resettlement policies, without adequate logistical and social preparedness, caused long-term setbacks in rural development and social integration.